Characteristics of adolescents referred for bariatric surgery in Abu Dhabi, United Arab Emirates - Beck, Reem Hassan; Afrooz, Imrana; Suhail Masalawala, Muhammad; Watad, Rama; Al Shaban, Talat; Deeb, Asma (Frontiers in Pediatrics, 2024)
About a third of children and adolescents are overweight or obese in the United Arab Emirates, and referrals for metabolic and bariatric surgery (MBS) are now common. Despite excellent evidence that MBS should be considered in adolescents with severe obesity, it remains a management approach of last resort in many cases. Baseline, real-world data on adolescent patients living with obesity referred for surgery, their characteristics, and how these relate to current and future referral policy are important to ensure best practice. Here we examined the demographic, anthropometric, and clinical characteristics of adolescents referred for MBS over a three-year period to Sheikh Shakhbout Medical City (SSMC), Abu Dhabi, UAE. Ninety-two adolescents living with obesity were recruited: 54.3% were female, the average age was 16.3 ± 2.4 years, and 88.0% of patients had a first-degree relative with a history of obesity and 62% a family history of bariatric surgery. The average BMI was 47.7 ± 10.5, and the average percentage of the 95 th percentile BMI was 169.5 ± 38.8%. Complications of obesity (hypertension, type 2 diabetes and prediabetes, dyslipidemia, and liver function abnormalities) were common. Our analysis highlights that there exists a mismatch between the profiles of patients referred for MBS, local guidelines, and international best practice in decisionmaking for referral to MBS services. While many adolescents in the UAE seem to enjoy family support and experience in the surgical management of obesity, local guidelines need updating to reflect changes in the definitions of obesity, thresholds for referral, and to remove unnecessary developmental stage barriers to increase the window for personalized surgical management.